MARSHALL CHARACTERISTICS ANALYSIS USING VARIATION WITHOUT BROKEN AND MANY FRACTURES OF GRAVEL ON MIXED HOT ROLLED SHEET - WEARING COURSE (HRS-WC) - Dela Permata Sari; Yasrudin Yasrudin (CERUCUK, 2022)
The asphalt pavement layer is composed of a mixture of coarse aggregate, medium aggregate, fine aggregate and asphalt. The use of coarse aggregate and medium aggregate derived from natural aggregates or rivers which are taken directly without the process of breaking the stone with a stone crusher (Stone Crusher) resulted in poor quality and will affect all Marshall test parameters. Therefore, research usinggravel without broken planes, one broken plane, two broken planes, and many cracked areas on coarse aggregate were carried out to determine the characteristics of gravel, and carried out Marshall testing to obtain optimal asphalt content, as well as analyzing the results of the comparison of Marshall characteristic values, among others, resistance (stability), plastic melting (flow), VIM, VMA, VFB, Marshall quotient (Marshall Quotient/MQ) and density of the HRS-WC mixture.The results of the study show The value of the optimum asphalt content in HRS-WC without cracks and many cracked areas is 6.5%, the density value between the HRS-WC asphalt mixture without cracked areas and the HRS-WC asphalt mixture with many cracked areas from the optimum asphalt content is the same value. The value of stability, flow, VFB, and Immersion Index of the HRS- WC asphalt mixture without cracks is smaller than the value of the HRS-WC asphalt mixture with many cracked areas. The value of VIM, VMA, and MQ of the HRS-WC asphalt mixture without cracks is greater than the value of the HRS-WC asphalt mixture with many areas.